Efek Limpahan dan Analisis Pusat Pertumbuhan Provinsi Kalimantan Tengah - Maria Christina Yuli Pratiwi (Jurnal Kebijakan Pembangunan, 2017)
Province of Central Kalimantan plays an important role in the national development and has the highest of economic growth in Kalimantan. The paper identifies which districts that have potency as the growth poles and determines the spatial spillover effects in Central Kalimantan during 2010-2016. Data ini this study uses secondary data and the social-economic data were collected for 14 districts. Using quantitative methods, in particular: Klassen Typology, scalogram analysis, geograpyl concentration analysis, gravity analysis, spatial autocorrelation, and spillover effect. The result of research finds that: (1) Kota Palangka Raya as the growth pole; (2) Kotawaringin Timur Regency dan Kotawaringin Barat Regency as the new growth pole; (3) the analysis of geographical concentrations shows that the facilities haven't been equally distributed in the districts of Province of Central Kalimantan; (4) the research results also hasn't been in accordance with the Spatial Plan (RTRW) of Central Kalimantan Province; (5) the economics growth concentration concentrated geographically in the western, middle, and eastern; and (6) Pulang Pisau Regency and Barito Selatan Regency have the biggest spillover effect. Abstrak Provinsi Kalimantan Tengah berperan penting dalam perekonomian nasional dan memiliki laju pertumbuhanekonomi tertinggi se-Kalimantan. Studi ini bertujuan untuk mengidentifikasi kabupaten/kota yang memilikipotensi sebagai pusat pertumbuhan dan mengetahui efek limpahan spasial selama periode 2010-2016. Datadalam studi ini adalah data sekunder yang dikumpulkan dari data sosial ekonomi 14 kabupaten/kota.Menggunakan metode kuantitatif deskriptif dan alat analisis: Tipologi Klassen, analisis skalogram, analisiskonsentrasi geografis, analisis gravitasi, autokorelasi spasial, dan efek spillover. Hasil studi menunjukkan:(1) Kota Palangka Raya merupakan pusat pertumbuhan; (2) Kabupaten Kotawaringin Timur danKotawaringin Barat merupakan daerah pusat pertumbuhan baru; (3) dalam analisis konsentrasi geografidiketahui bahwa fasilitas-fasilitas belum terdistribusi secara merata di kabupaten/kota Provinsi KalimantanTengah; (4) hasil penelitian belum sesuai dengan Rencana Tata Ruang Wilayah Provinsi Kalimantan Tengah;(5) konsentrasi pertumbuhan ekonomi tersebar di bagian barat, tengah, dan timur; dan (6) Kabupaten PulangPisau dan Kabupaten Barito Selatan adalah daerah dengan nilai spillover effect terbesar